2012
DOI: 10.1128/aac.01242-12
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic and Pharmacodynamic Modeling of Amodiaquine and Desethylamodiaquine in Women with Plasmodium vivax Malaria during and after Pregnancy

Abstract: f Amodiaquine is effective for the treatment of Plasmodium vivax malaria, but there is little information on the pharmacokinetic and pharmacodynamic properties of amodiaquine in pregnant women with malaria. This study evaluated the population pharmacokinetic and pharmacodynamic properties of amodiaquine and its biologically active metabolite, desethylamodiaquine, in pregnant women with P. vivax infection and again after delivery. Twenty-seven pregnant women infected with P. vivax malaria on the Thai-Myanmar bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
44
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 64 publications
(96 reference statements)
8
44
1
Order By: Relevance
“…Enzyme auto-induction cannot be excluded as an underlying cause to the time-dependent difference in exposure. However, previous detailed PK studies of oral and parenteral administration of ARS have demonstrated a clear malaria effect on the relative bioavailability thought to result from reduced first pass metabolism (40,41). The decreased absorption rate with increasing parasite density was unexpected and opposite to previous observations (39,(42)(43)(44)(45)(46)(47)(48).…”
Section: Population Pharmacokineticscontrasting
confidence: 55%
“…Enzyme auto-induction cannot be excluded as an underlying cause to the time-dependent difference in exposure. However, previous detailed PK studies of oral and parenteral administration of ARS have demonstrated a clear malaria effect on the relative bioavailability thought to result from reduced first pass metabolism (40,41). The decreased absorption rate with increasing parasite density was unexpected and opposite to previous observations (39,(42)(43)(44)(45)(46)(47)(48).…”
Section: Population Pharmacokineticscontrasting
confidence: 55%
“…One study in healthy G6PD normal children aged 5–12 years from Papua New Guinea found PQ–PK characteristics equivalent to those in adults [66]. This is a potentially significant finding because a failure to appreciate that children have higher clearance rates of some antimalarial drugs compared to adults has resulted in under dosing of sulfadoxine-pyrimethamine and DHAPP [70, 71]. The Papua New Guinea data support the use of the same mg base/kg dose range for adults and children as young as 5 years and should result in comparable OM exposures.…”
Section: Introductionmentioning
confidence: 99%
“…Blood dyscrasias were not a problem associated with its use. A pharmacokinetics study on AQ for treatment of P.vivax in pregnancy conducted in Thailand indicates the doses are similar to that of non-pregnant adults 131,135…”
Section: Prevention and Treatmentmentioning
confidence: 99%